Reorientation of Gender Politics in the Patriarchal System of Society - Ramdhani, Hilal (Law Research Review Quarterly, 2018)
The democratic system of government implies that there are equal rights in general elections between men and women. The concept of democracy which should originate from western thought faces challenges and obstacles to be applied in Indonesia, especially in patriarchal systems of society that focus on the role of men. The reality of a patriarchal system of society is to position women as a party below men, so women will find it difficult to develop themselves in a democratic political constellation with a one man one vote system. This study uses a qualitative approach with the case study method of simultaneous regional head elections in West Java, the urgency of conducting research in West Java because it has a patriarchal community system, and the election of the governor's head in West Java in 2018 there are no female candidates. The results of the research focus on the formation of an effective and efficient political education model to reorient leadership in West Java. The results of this study are aimed at ensuring that women in West Java have confidence in following the democratic political constellation.